THE LOCAL ADMINISTRATION SYSTEM IN THE HASHEMITE KINGDOM OF JORDAN - Othman Khalaf Lafee AlHammad (Scholar Express Journals, 2021)
The research aims to shed light on the local administration in Jordan, by highlighting the important role of municipalities in Jordan, clarifying the concepts associated with them, and helping to evaluate and develop the administrative reality of municipalities in Jordan. With an indication of the extent of the application of the decentralization approach, and the most important problems and difficulties that this application faced in Jordan. The study concluded that Jordan's adoption of the administrative decentralization approach and its application in the field of municipalities is still in its infancy and needs to complete its legal and administrative framework on the one hand, and overcome the difficulties it is experiencing on the other hand. The research recommended strengthening the role of municipalities and their programs in achieving sustainable development in its various fields, introducing the concept of sustainability in their development programs, working on developing the administrative reality of municipalities, and developing the legal environment regulating the relationship between the Ministry of Local Administration and the municipalities
Keywords: Local Administration; Jordan; Administrative Reality; Municipalities